29 The impact of teicoplanin in prevention of implantable cardiac electrical devices infection. A single centre quality improvement audit. (October 2018) - Pharithi, RB; Flynn, P; Murphy, L; Hensey, M; O'Hare, D; Mubarak, S; Rathore, F; Omar, M; Morad, S; Cadogan, D; Quinn, M; McCreery, C; et al.
Abstract : Background: Infection of implantable cardiac electrical devices (ICEDs) is associated with increased morbidity and mortality. The rates are higher with devices' replacement than with primary device implantation. Aims and objectives: The aim of this project was to identify the rates of ICEDs and develop and implement strategies to reduce ICEDs infection in our centre in compliance with best practice. Methods: This is a complete audit cycle completed in a cardiac tertiary centre to assess the impact of change from cefuroxime 1.5 g to Teicoplanin 10 mg/kg as our prophylactic antibiotic for device implantation. A total of 314 patients were involved. The first part of audit from 28/04/2016 to 07/3/2017 and re-auditing was from 1/8/2017 to 31/3/2018. The main devices reviewed were primary Cardiac Re-synchronization therapy devices (CRTs), primary implantable cardiac defibrillators/permanent pacemakers (ICD/PPM), and All CRTs, PPM, and ICD generators changes. We also reviewed Implantable loop recorders for best practice even though no prophylactic anti-biotics were required for their implantation. Results: First part of the audit. 208 devices were implanted during this period. There were 9 (4.4%) infected ICEDs and had to be explanted. Only 4 of 9 (44.4%) had positive blood cultures. Figure 1 summarises the most likely risk factors. Intervention Pre-procedure antibiotics, cefuroxime 1.5 mg given less an hour prior to device implantation was changed to Teicoplanin 10 mg/kg rounded to the nearest 200 mg. Re-audit 108 devices were implanted. The rate of ICED infections had decreased from 4.4% to 0% (p≤0.05) by 31st March 2018. Figures 2a and 2b compares all the ICED implanted during the audit cycle. Figure 3 illustrates the results post prophylactic anti-biotic change. Discussion and conclusion: Continuous audit for quality improvement is beneficial, important and should always be encouraged. Teicoplanin is better than Cefuroxime as a prophylactic antibiotic in prevention of cardiac implantable electrical devices.